Optimization of Flow Rate TEG (Triethylene Glycol) in Absorbing Water Levels in Glycol Contactor (V-5400) With ASPEN HYSYS Simulation - Muhammad Ihsan (Newinera Publisher, 2022)
The purpose of this research is to determine the amount of TEG flow rate required to get dry gas with a moisture content consistent with industry requirements and to determine how much water content is absorbed in dry gas after TEG flow rate optimization. The glycol contactor (V-5400) is the primary piece of equipment for this activity, and the materials are dry gas and TEG solution in the dehydration unit. The research method employed is descriptive quantitative simulation via the use of the Aspen HYSYS V8.8 application tool. According to the simulation findings on the glycol contactor (V-5400) using Aspen HYSYS, in order to get dry gas with a moisture content of 4-7 lb/MMscf, a TEG solution with a flow rate of 2.4 ft3/min and a water content of 2.4 ft3/min is required. absorbed following flow rate optimization TEG is used to convert 7.6026 lb/MMscf water content to 6.7881 lb/MMscf water content with a percentage difference of 0.8145, but real data converts 7.4702 lb/MMscf water content to 6.6984 lb/MMscf water content with a percentage difference of 0.7718.